NuSTAR and Parkes observations of the transitional millisecond pulsar binary XSS J12270–4859 in the rotation-powered state. Issue 4 (21st January 2020) - de Martino, D; Papitto, A; Burgay, M; Possenti, A; Coti Zelati, F; Rea, N; Torres, D F; Belloni, T M
ABSTRACT: We report on the first NuSTAR observation of the transitional millisecond pulsar binary XSS J12270–4859 during its current rotation-powered state, complemented with a 2.5 yr-long radio monitoring at Parkes telescope and archival XMM–Newton and Swift X-ray and optical data. The radio pulsar is mainly detected at 1.4 GHz displaying eclipses over 40 per cent of the 6.91 h orbital cycle. We derive a new updated radio ephemeris to study the 3–79 keV light curve that displays a significant orbital modulation with fractional amplitude of 28± 3 per cent, a structured maximum centred at the inferior conjunction of the pulsar and no cycle-to-cycle or low–high-flaring mode variabilities. The average X-ray spectrum, extending up to ∼70 keV without a spectral break, is well described by a simple power law with photon index Γ = 1.17 ± 0.08 giving a 3–79 keV luminosity of 7.6_-0.8^+3.8 × 10^32 erg s^-1 for a distance of 1.37_-0.15^+0.69 kpc. Energy resolved orbital light curves reveal that the modulation is not energy dependent from 3 to 25 keV and is undetected with an upper limit of 10 per cent above 25 keV. Comparison with previous X-ray XMM–Newton observations in common energy ranges confirms that the modulation amplitudes vary on time-scales of a few months, indicative of a non-stationary contribution of the intrabinary shock (IBS) formed by the colliding winds of the pulsar and the companion. A more detailed inspection of energy resolved modulations than previously reported gives hints of a mild softening at superior conjunction of the pulsar below 3 keV, likely due to the contribution of the thermal emission from the neutron star. The IBS emission, if extending into the MeV range, would be energetically capable alone to irradiate the donor star.